Hydrogen‐Enhanced Catalytic Conversion of Amorphous Carbon to Graphene for Achieving Superlubricity. Issue 10 (15th January 2023) - Li, Ruiyun; Yang, Xing; Ma, Ming; Zhang, Junyan
Abstract: The solid‐state conversion of amorphous carbon into graphene is extremely difficult, but it can be achieved in the friction experiments that induce macroscale superlubricity. However, the underlying conversion mechanisms remain elusive. Here, the friction experiments with Cu nanoparticles and (non‐hydrogen (H) or H) a‐C in vacuum, show the H‐induced conversion of mechanical to chemical wear, resulting in the a‐C's tribosoftening and nanofragmentating that produce hydrocarbon nanoclusters or molecules. It is such exactly hydrocarbon species that yield graphene at hydrogen‐rich a‐C friction interface, through reaction of them with Cu nanoparticles. In comparison, graphene isn't formed at Cu/non‐H a‐C friction interface. Atomistic simulations reveal the hydrogen‐enhanced tribochemical decomposition of a‐C and demonstrate the energetically favorable graphitization transformation of hydrocarbons on Cu substrates. The findings are of importance to achieve solid‐state transformation between different carbon allotropes and provide a good strategy to synthesize other graphitic encapsulated catalysts with doped elements. Abstract : By the hydrocarbon nanoclusters or molecules formation in the H‐enhanced tribosoftening and nanofragmentating process of a‐C, graphene is formed on the Cu nanoparticles. Macroscale superlubricity (0.007) is achieved on a‐C surfaces by graphene encapsulated Cu nanoparticles.